An evaluation of a youth-development-through-sport programme - Mendoza, Cynthia (Institute for Monitoring and Evaluation, 2017)
This evaluation was based on a youth-development-through-sport programme in Africa. In the present study the Success Case Method was used to demonstrate initial changes experienced by participants in the training and to inform the Youth Empowerment through Sport (YES) programme about quick and effective modifications that could be made to it. Several evaluation questions enquired what courses participants were using to achieve results at their projects, what barriers prevented participants from using the skills from training and what the quality of the training programme was like. Questions were also asked as to whether there were aspects of the programme that could be improved. Results revealed that the YES programme improved personal development and sessions at the participant's project through good leadership. There was also evidence that longer term outcomes were achieved, including increased employability. At the same time, there is a lot of valuable information in the report that highlights where the programme could focus its effort to maximize the potential of future impact that could be achieved.